PENGARUH LATIHAN STANDING ISO TOE RAISE TERHADAP KEKUATAN OTOT TUNGKAI PADA TIM VOLI PUTRA SMK NEGERI 5 PEKANBARU - Fendi Riakurniawan Riakurniawan; Ramadi '; Ardiah Juita Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract The problems raised in this research is the effect of the training Standing Iso Toe Raise against the muscles strength in men’s volleyball SMK Negeri 5 Pekanbaru. The research aims to determine the effect of Standing Iso Toe Raise against the muscles strength in men’s volleyball SMK Negeri 5 Pekanbaru.These research is experimental. The research was conducted in Pekanbaru SMK Negeri 5. The sample of this study of 12 people. Data were collected through the initial test and final test leg with leg muscle strength dynamometer . The data were analyzed comperatif, then further research is done to test the hypothesis that has been asked in the problem, namely: there are Standing Iso Toe Raise training effect on leg muscles strength SMK Negeri 5 men’s volleyball team Pekanbaru.Based on t test analysis produces large thitung 5,02 and as much as 1,796 ttabel. Means thitung > ttabel. It can be concluded that Ho denied and Ha accepted. It can be concluded that there is no significant effect of the training Body Standing Iso Toe Raise leg muscle strength ( X ) leg muscles strength (Y ) In the men’s volleyball team SMK Negeri 5 Pekanbaru. Keywords : Standing Iso Toe Raise, Leg Muscle Strength